The Assistance Model of the Baitul Mal in Promoting The Community of Home Industry - Sabirin,; Masriza,; Zainuddin, Muslim; Zulyadi, Teuku; Husna, Nurul; Drani, Syazwani (International Journal of Criminology and Sociology, 2022)
Baitul Mal as an institution for collecting and distributing zakat, infaq, and shadakah among Muslims, has not yet developed community economic programs, especially home industries. Although the community economic development program has been implemented, the assistance model provided so far has not been able to provide increased income for the community. This article responds to the view that Baitul Mal in carrying out its programs is only consumptive in nature and has not been able to develop productive programs related to the community's economy by providing venture capital for home industry players. This qualitative research in finding a model of Baitul Mal assistance was done through observation, interviews, and documentation. The data obtained is used to strengthen the research objectives in supporting the assistance model for the assistance of Baitul Mal Aceh. This study found that the Baitul Mal Aceh program was more dominant in the field of consumptive zakat, while the assistance model of Baitul Mal assistance in the form of productive zakat had not been able to provide maximum results for the economic development of the community, especially in the home industry sector. So in the future, there needs to be an improvement, as an initial solution in introducing the Baitul Mal Aceh assistance model to the community.